Subaponeurotic ligation of communicating leg veins: Technique - Gateño, Nisso; Delgado, Bolivar; Nozar, José; Piñeyro, Alberto (Cirugía del Uruguay, 1979)
Case material consists of 100 operations. The paper describes surgical technique for subaponeurotic ligation of communicating veins in lower limb.